MEASURING RELATIVE EFFICIENCIES IN THE SHOE INDUSTRY SECTOR IN COLOMBIA: A DEA APPROACH/MIDIENDO LAS EFICIENCIAS RELATIVAS DE LA INDUSTRIA DEL CALZADO EN COLOMBIA: UN ENFOQUE DEA (2011)
ABSTRACTEVA® (Economic Value Added) is a commonly used financial indicator that measures the real profitability of a firm for a specific period of time. The main concept behind EVA® is that the real profitability of the firm is a function of its cost of capital, net operational profits after taxes (NOPAT) and the invested capital in the firm (IC). Is within this context that we used Data Envelopment Analysis (DEA) to analyze the financial data from 75 companies of the Colombian Shoe Industry Sector, in order to find which input factor (NOPAT or IC) is more relevant in maximizing the EVA® of the firm. Our findings indicate that for the years 2007-2006, the most important factor for maximizing EVA® in the Colombian shoe sector was invested capital and that for the years 2005-2004 was NOPAT.RESUMENEVA® (Valor Económico Agregado) es una medida de desempeño comúnmente utilizada para medir la rentabilidad real de una compañía por un periodo especifico de tiempo. El atractivo del EVA® radica en su facilidad de cálculo y en el hecho que mide la rentabilidad real de la firma como una función del costo de capital, la utilidad operacional después de impuestos y el capital invertido en esta. Es dentro de este contexto que se utilizo el Análisis Envolvente de Datos (DEA) para analizar la información financiera de 75 compañías del sector del calzado en Colombia. Esto con el propósito de determinar que factor de la fórmula del EVA® es el que más relevancia tiene en la maximización del EVA®. El resultado obtenido fue que para el periodo 2007-2006 el factor más relevante fue el capital invertido y para el año 2005-2004 fue la utilidad operacional después de impuestos.